2007
DOI: 10.1093/ecam/nem020
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Treatment of Dysmenorrhea Resistant to Conventional Medical Treatment

Abstract: We evaluated the effect of acupuncture on NSAID resistant dysmenorrhea related pain [measured according to Visual Analogue Scale (VAS)] in 15 consecutive patients. Pain was measured at baseline (T1), mid treatment (T2), end of treatment (T3) and 3 (T4) and 6 months (T5) after the end of treatment. Substantial reduction of pain and NSAID assumption was observed in 13 of 15 patients (87%). Pain intensity was significantly reduced with respect to baseline (average VAS = 8.5), by 64, 72, 60 or 53% at T2, T3, T4 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 20 publications
1
15
1
3
Order By: Relevance
“…Acupuncture at such acupoints as Taixi(KI-3), Gongsun(SP-4), Zusanli(ST-36), Tianshu(ST-25), Guilai(ST-29), Qichong(ST-30), Guanyuan(CV-4) can be used to treat dysmenorrhea, especially to treat those subjects in whom oral contraceptives are contraindicated or refused (Iorno et al, 2008). Li, et al (Li et al, 2008) observed the therapeutic effect of acupuncture at Siguan points with Qinglong Baizei method on primary dysmenorrhea and to explore the mechanism.…”
Section: Dysmenorrheamentioning
confidence: 99%
“…Acupuncture at such acupoints as Taixi(KI-3), Gongsun(SP-4), Zusanli(ST-36), Tianshu(ST-25), Guilai(ST-29), Qichong(ST-30), Guanyuan(CV-4) can be used to treat dysmenorrhea, especially to treat those subjects in whom oral contraceptives are contraindicated or refused (Iorno et al, 2008). Li, et al (Li et al, 2008) observed the therapeutic effect of acupuncture at Siguan points with Qinglong Baizei method on primary dysmenorrhea and to explore the mechanism.…”
Section: Dysmenorrheamentioning
confidence: 99%
“…However, NSAIDs may lead to many adverse effects, including indigestion, headache, and drowsiness, and their rate of failure to reduce dysmenorrhea may reach 20% [5]. Therefore, complementary and alternative medicine (CAM) is becoming an increasingly popular choice for alleviation of dysmenorrhea [613]. …”
Section: Introductionmentioning
confidence: 99%
“…They were obtained from McGill questionnaire based on PRI and VAS for assessing the future and PPI. Several studies verified these evidence (1,14,(32)(33)(34). There are 3 lines to the control of primary dysmenorrhea including pharmacological, nonpharmacological, and surgical lines (5).…”
Section: Discussionmentioning
confidence: 78%
“…In that study, stretch and muscle relaxation techniques were proved to be effective in reducing dysmenorrhea symptoms and the VAS decreased in physiotherapy group in third menstrual cycle (12,35). Furthermore, some research indicated the effect of acupuncture in the treatment of dysmenorrhea when there was contraindication for using NSAID or oral contraceptive (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 92%